Exploring blood immune cells in the protective effects of gut microbiota on rheumatic heart disease based on Mendelian randomization analysis - Juexiu LU; Yujie Huang; Yangguang Yin; Biqiong Tang (Scientific Reports)
Abstract Rheumatic Heart Disease (RHD) remains a significant health burden, particularly in regions with scarce healthcare resources, research on its immunological aspects remains insufficient. This study employed a two-sample Mendelian Randomization approach, utilizing GWAS data from the largest available datasets for gut microbiota and immune cells as exposures, with outcome data for Rheumatic Valve Diseases (RVD) and Rheumatic Heart Disease affecting other parts of the heart (RHD-other) obtained from the FinnGen study. The primary analytical method was the Inverse Variance Weighted (IVW) approach, complemented by heterogeneity analyses and MR-Egger regression to assess horizontal pleiotropy. Furthermore, a two-step mediation analysis was conducted to investigate the potential mediating role of immune cells in the association between gut microbiota and RHD. This study revealed significant inverse associations between gut microbiota abundance and Rheumatic Heart Disease (RHD) risk. Specifically, the gut abundance of genus Blautia was negatively correlated with RHD-other risk (P_IVW: 0.00932, OR [95%CI]: 0.000734[3.22e-06, 0.16937]), and genus Ruminococcaceae UCG005 showed a similar negative association (P_IVW: 0.038, OR [95%CI]: 0.165[0.02994, 0.90811]). Additionally, the proportions of CD4-CD8- T cell %leukocyte and CD4-CD8- T cell %T cell were inversely related to RHD-other risk (P_IVW: 0.02222, OR [95%CI]: 5.08027 [1.26133, 20.46191] and P: 0.01601, OR[95%CI]: 6.55576 [1.4196, 30.27582], respectively). Moreover, IgD on IgD + CD24 + B cells was found to be negatively correlated with RHD-other risk (P_IVW: 0.01867, OR [95%CI]: 2.17171 [1.1380, 4.14443]). The study also highlighted the protective effects of gut microbiota through mediation analyses: Blautia’s impact via IgD on IgD + CD24 + B cells showed a mediation proportion of 8.62514%; Ruminococcaceae UCG005’s influence via CD4-CD8- T cell %T cell and CD4-CD8- T cell %leukocyte resulted in mediation proportions of 35.25817% and 30.86827%, respectively. Significant inverse associations were observed between gut microbiota abundance and risk of Rheumatic Heart Disease (RHD), with specific findings for Rheumatic Valve Disease (RVD) and RHD affecting other parts of the heart (RHD-other). For RHD-other, higher abundance of Blautia (OR: 0.0007, 95% CI: 3.22e-06 to 0.169, p = 0.009) and Ruminococcaceae UCG005 (OR: 0.165, 95% CI: 0.030 to 0.908, p = 0.038) were associated with lower risk. Additionally, lower proportions of CD4-CD8- T cells (%leukocyte and %T cell) and IgD on IgD + CD24 + B cells were inversely related to RHD-other risk (ORs: 5.08 and 6.56, p = 0.022 and p = 0.016, respectively). For RVD, higher abundance of Candidatus Soleaferrea was protective (OR: 0.670, 95% CI: 0.460 to 0.976, p = 0.037), while higher levels of CD11c on granulocytes were associated with increased risk (OR: 1.310, 95% CI: 1.023 to 1.679, p = 0.032). Mediation analyses indicated that gut microbiota influence RHD risk through distinct immune pathways, with Blautia affecting RHD-other via IgD on B cells (8.62% mediation), Ruminococcaceae UCG005 via CD4-CD8- T cells (%T cell: 35.26%, %leukocyte: 30.87%). Genus Candidatus Soleaferrea affecting RVD through CD11c on granulocyte (15.01% mediation). The study concludes that higher gut abundance of Candidatus Soleaferrea protects against RVD through the mechanism involving CD11c on granulocytes. Additionally, Blautia exerts a protective effect against RHD-other through its influence on IgD on IgD + CD24 + B cells. Similarly, the abundance of genus Ruminococcaceae UCG005 provides protection against RHD-other by influencing CD4-CD8- T cell %T cell and CD4-CD8- T cell %leukocyte.